A case of sudden brain metastases progression after temporary targeted therapy discontinuation: when to regret a drug holiday. Issue 2 (April 2021) - Indini, Alice; Rijavec, Erika; Mandalà, Mario; Castiglioni, Simona; Beltramo, Giancarlo; Grossi, Francesco
Abstract : Targeted therapy improves outcomes in BRAF V600 -mutant metastatic melanoma with active brain metastases. We present the case of a patient with rapid brain disease progression upon temporary targeted therapy discontinuation and unusual rapid disease response upon treatment resumption. This report presents a 78-year-old woman with metastatic BRAF V600E positive melanoma (bladder and brain localizations). The patient started first-line dabrafenib and trametinib with good tolerability and evidence of complete response (CR). After 8 months of maintained CR, the patient took a drug holiday for 14 days. Brain MRI performed after treatment pause showed extensive disease progression, whereas extracranial staging was negative. The patient was asymptomatic: she restarted targeted therapy and underwent evaluation for whole-brain radiotherapy. Brain computed tomography scan and subsequent MRI performed to plan radiotherapy showed brain CR after only 10 days of targeted therapy resumption. The patient continued treatment, and radiotherapy indication was withheld. Repeated brain MRI confirmed maintained CR. Treatment with dabrafenib and trametinib is ongoing with excellent tolerability. Rapid intracranial progression is a well-known finding after discontinuation of combined targeted therapy in the case of extracranial progressive disease. This is the first report of documented disease progression upon temporary treatment discontinuation for reasons other than toxicity, with an unusual response after retreatment. Caution should be used in tailoring treatment during targeted therapy, allowing pauses for reasons other than toxicity. Strict adherence to treatment is paramount to guarantee disease control.